SAARC Academy of Ophthalmology – Tailoring Clinical Standards for Diabetic Retinopathy Care to Available Resources - Pradhan, Eli; Nag, Dipak; Wewalwala, Deepanee; Pokharel, Subash; Conroy, Dolores; Pradhana, Divya; Srinivasan, Ramyaa; Sivaprasad, Sobha; Azad, Rajavardhan; Khaqan, Hussain Ahmad; Rai, Bhim; Frogh, Haji Hussain; et al. (Nepalese Journal of Ophthalmology, 2022)
The South Asian Association for Regional Cooperation (SAARC) is a geopolitical union of 8 member states of South Asia, one of the rapidly transforming regions in the world. It houses 25% of the world population, with a similar rise in at-risk population for diabetes and its complications. Diabetic retinopathy (DR), is one of the major causes of blindness and visual impairment. Despite the region’s dramatic demographic and economic transformation, its healthcare system is nascent enough to achieve the over-reaching recommendations by developed countries. Our review helps in tailoring the clinical care to the available resources, focusing on an integrated approach for timely detection and management of sight-threatening diabetic retinopathy (STDR). Our study also recommends urgent measures to be taken to implement diabetes registers by all care providers and take the responsibility of ensuring that patients with STDR are referred for treatment. This tailored framework helps in the screening and treatment of those with STDR in resource-constrained settings, thereby decreasing the health and economic burden in all SAARC countries.